Blended learning for engineering education 4.0: Students' perceptions and their learning difficulties - Low M.C.; Lee C.K.; Sidhu M.S.; Lim S.P.; Hasan Z.; Lim S.C. (John Wiley and Sons Inc, 2024)
Engineering education plays a vital role in nurturing high-quality engineers to meet the demands of the industry. The advancement in Information and Communication Technology (ICT) has provided greater potential as a supporting tool in engineering education. Previous research has emphasized the need to further investigate the learning difficulties faced by engineering students to enhance their learning experience. Although the implementation of blended learning using the flipped classroom approach has gained popularity in tertiary education, there is a lack of research on students' perception of this approach in engineering education. This exploratory study focuses on the Engineering domain, specifically investigating students' learning difficulties in Mechanics Dynamics and their attitudes toward blended learning using the flipped classroom approach in engineering education. Using data collected from 121 students at Universiti Tenaga Nasional (UNITEN), Malaysia, this study employed descriptive statistics and multiple linear regression to analyze the data. Three models related to students' learning difficulties were proposed based on the outcomes of exploratory factor analysis. The results indicate that students encountered difficulties in learning Mechanics Dynamics, particularly in visualizing concepts and solving problems involving three dimensions. The findings and analysis demonstrate significant results (p <.05), supporting the hypotheses of the three proposed models. Additionally, the majority of students (66.1%) exhibited a positive attitude toward the use of the flipped classroom approach in engineering courses. The research findings serve as a preliminary requirement for the development of a software prototype to investigate the efficacy of the flipped classroom approach in engineering courses. 2023 Wiley Periodicals LLC.